Carotid Body Tumor: A Rare Case Report of a Neck Tumor - Andinata, Bob; Marleen, Stella; Partahi, Jeremy Romeo (http://dharmais.co.id/, 2024)
Introduction: Commonly referred to as paragangliomas or glomus caroticum, carotid body tumors (CBT) are rare tumors that develop close to the carotid artery’s branching point and are generally benign. Only 0.6% of all head and neck tumors in humans are CBT, which are rare malignancies of chemical receptors. The surgical classification presented by Shamblin et al. is a significant turning point in assessing the resectability of these tumors. These tumors are frequently diagnosed and surgically prepared using magnetic resonance imaging, which provides crucial information for surgical planning. The purpose of this case report was to describe the diagnosis and treatment of CBT.Case Presentation: A 26-year-old woman with a carotid body tumor is presented. She had a painless, progressively growing bulge on the right side of her neck. The patient previously had a history of a lump appearing in the same location and was operated in 2015; the results of anatomic pathology were non-specific chronic lymphadenitis. The diagnosis was made based on history, and clinical and radiological examination findings. The results from the MRI were a mass in the right carotid bifurcation region to the right carotid space. Therefore, surgical excision was performed. Conclusions: Surgical excision was performed after the carotid body tumor was determined to be Type I according to Shamblin’s categorization. The conclusion of the histopathology report was histologic consistent with Schwannoma. The patient showed no signs of surgical complications. Comprehensive surgical methods reduce the possibility of complications and ensure a safe resection.n’s type I, surgical exicision